A day in the life of winter plankton: under-ice community dynamics during 24 h in a eutrophic lake. (24th September 2021) - Chiapella, Ariana M; Grigel, Haley; Lister, Hannah; Hrycik, Allison; O'Malley, Brian P; Stockwell, Jason D
Abstract: Although diel vertical migration (DVM) in aquatic systems may account for the largest daily migration of biomass globally, our understanding of this process under ice cover is limited, particularly in fresh water. The date of lake ice onset and duration of ice cover is declining globally, therefore determining the extent of plankton migrations under ice is imperative to inform our baseline understanding of seasonal differences in community structure and function, and how conditions may change over time. We investigated whether plankton exhibit DVM under ice and explored interactions between phytoplankton and zooplankton at highly resolved space–time scales across 24 h in a eutrophic system. Despite the dominance of motile taxa, phytoplankton remained vertically segregated based on morpho-functional groups throughout the sampling period. Daphnia mendotae exhibited size-structured DVM with an upward migration at sunset and sunrise, and midnight sinking, presumably to avoid the rise of predatory Chaoborus . We hypothesize that because overwintering daphnids require rich lipid stores, D. mendotae migrated to access small, lipid-rich phytoplankton that were limited to surface waters. Given our study took place during an unusually warm winter in a eutrophic system, our results may represent future under-ice dynamics under increasing eutrophication pressure and climate warming in shallow lakes.